The Overlooked Zoonotic Disease Leptospirosis: Three Case Reports in Eastern Turkey - Sagmak Tartar, Ayse; Asan, Mehmet Ali; Udurgucu, Hatice; Akbulut, Ayhan; Demirdag, Kutbeddin (Bilimsel Tip Yayinevi, 2021)
Leptospirosis is a zoonotic infection, which is considered to be the most common in the world, caused by spirochetes of the genus Leptospira. It is most commonly transmitted to humans by contact of rodent urine-contaminated water with damaged skin and mucous membranes. The diagnosis of leptospirosis should be considered in the differential diagnosis of fever, jaundice, thrombocytopenia and acute renal failure, especially in those working in occupations in the risk group. In the cases we presented, it was aimed to emphasize that leptospirosis should be considered in the presence of epidemiological history.
Keywords: Leptospirosis; Icterohemorrhage; Weil